Design a course supported with multimedia and online learning: the adaptation as a fundamental. - Chenoll Mora, Antonio (2015)
In this work we are going to share some reflections on learning in general and on the learning of foreign languages in particular, both of which are dependent on the context in several levels, learning styles, and both the input and output material's format. We will confer an essential role to the discernment between informal and formal learning as a means to the development of a lifelong learning capability. Since we consider real learning to be built on the basis of social and personal research experiences we will consider this capability as an element to bear in mind when designing an online course and one as much or even more important than the acquisition of contents. Let us not forget that the development of cognitive learning abilities is essential.